Stosunki transatlantyckie - Baran, Bernadeta (Transatlantic Relations, 2008)
Transatlantic relations have been recently characterized as strained, especially due to divergent positions on the Iraq war which prominent European nations, including France and Germany opposed. Another major issue is reducing pollution with the Kyoto protocol, which the whole European Union supports and the United States opposes. But, besides the political plane, there are economic relation between the USA and the EU which are the most important in the world. Both parties had recently decided to overcome the previous animosity. Co-operation seems to be very important nowadays, especially during the lasting changes of global power relations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 219-235